Safety and Accuracy of Freehand Pedicle Screw Placement and the Role of Intraoperative O-Arm: A Single-Institution Experience. Issue 3 (1st February 2023) - Alomari, Safwan; Lubelski, Daniel; Lehner, Kurt; Tang, Anthony; Wolinsky, Jean-Paul; Theodore, Nicholas; Sciubba, Daniel M.; Larry Lo, Sheng-fu; Belzberg, Allan; Weingart, Jon; Witham, Timothy; Gokaslan, Ziya L.; et al.
Abstract : Study Design: Retrospective cohort study. Objective: The aim was to investigate the accuracy of pedicle screw placement by freehand technique and to compare revision surgery rates among three different imaging verification pathways. Summary of Background Data: Studies comparing different imaging modalities in freehand screw placement surgery are limited. Materials and Methods: A single-institution retrospective chart review identified adult patients who underwent freehand pedicle screw placement in the thoracic, lumbar or sacral levels. Patients were stratified into three cohorts based on the intraoperative imaging modality used to assess the accuracy of screw position: intraoperative X-rays (cohort 1); intraoperative O-arm (cohort 2); or intraoperative computed tomography (CT)-scan (cohort 3). Postoperative CT scans were performed on all patients in cohorts 1 and 2. Postoperative CT scan was not required in cohort 3. Screw accuracy was assessed using the Gertzbein-Robbins grading system. Results: A total of 9179 pedicle screws were placed in the thoracic or lumbosacral spine in 1311 patients. 210 (2.3%) screws were identified as Gertzbein-Robbins grades C-E on intraoperative/postoperative CT scan, 137 thoracic screws, and 73 lumbar screws ( P <0.001). Four hundred and nine patients underwent placement of 2754 screws followed by intraoperative X-ray (cohort 1); 793 patients underwent placement of 5587 screws followed by intraoperative O-arm (cohort 2); and 109 patients underwent placement of 838 screws followed by intraoperative CT scan (cohort 3). Postoperative CT scans identified 65 (2.4%) and 127 (2.3%) malpositioned screws in cohorts 1 and 2, respectively. Eleven screws (0.12%) were significantly malpositioned and required a second operation for screw revision. Nine patients (0.69%) required revision operations: eight of these patients were from cohort 1 and one patient was from cohort 2. Conclusion: When compared to intraoperative X-ray, intraoperative O-arm verification decreased the revision surgery rate for malpositioned screws from 0.37% to 0.02%. In addition, our analysis suggests that the use of intraoperative O-arm can obviate the need for postoperative CT scans.